Is H3K4me3 instructive for transcription activation? - Howe, Françoise S.; Fischl, Harry; Murray, Struan C.; Mellor, Jane (BioEssays, 2017)
Tri‐methylation of lysine 4 on histone H3 (H3K4me3) is a near‐universal chromatin modification at the transcription start site of active genes in eukaryotes from yeast to man and its levels reflect the amount of transcription. Because of this association, H3K4me3 is often described as an ‘activating’ histone modification and assumed to have an instructive role in the transcription of genes, but the field is lacking a conserved mechanism to support this view. The overwhelming finding from genome‐wide studies is that actually very little transcription changes upon removal of most H3K4me3 under steady‐state or dynamically changing conditions, including at mammalian CpG island promoters. Instead, rather than a major role in instructing transcription, time‐resolved experiments provide more evidence supporting the deposition of H3K4me3 into chromatin as a result of transcription, influencing processes such as memory of previous states, transcriptional consistency between cells in a population and transcription termination. The so‐called activating histone modification H3K4me3 correlates strongly with transcription, yet, the transcription of only a minority of genes changes when H3K4me3 is reduced. Instead, at most genes H3K4me3 may be deposited as a result of transcription to regulate post‐transcriptional processes such as transcriptional memory and gene expression noise.